How artificial intelligence tools influence customer experience and avoidance of similarity - Loureiro, S. M. C.; Ferreira, M. M.; Bilro, R. G.; Marques, L. (2023 Global Marketing Conference at Seoul: Marketing and management transformation in the challenging digital environment, 2023)
The capability for Artificial Intelligence in the beauty industry is enormous, as customers are demanding increasingly customized offers that only these strategies can offer. However, there is still a scarcity of empirical research on customer experiences enabled by AI, which highlights this research's relevance, which we intend to bridge.